Responses of the gastrointestinal microbiota to the protein metabolism of pond-cultured Japanese flounder (Paralichthys olivaceus) - Jiang, Yan; Wang, Jun; Lin, Lin; Xu, Yongjiang; Cui, Aijun; Wang, Kaijie; Liu, Xuezhou; Wang, Bin (Frontiers in Marine Science, 2023)
Protein metabolism can provide energy for various biological activities of organisms. However, there have been few studies on the succession of gastrointestinal microbiota structure during the metabolism of protein by the host. In this study, physiological and biochemical, qRT-PCR, and 16S rDNA high throughput sequencing methods were used to detect the activity characteristics of proteases and the related gene expression levels in each gastrointestinal tissue, as well as the distribution characteristics and succession of the gastrointestinal microbiota structure of pond-cultured Japanese flounder (Paralichthys olivaceus). The results showed that the activity of pepsin, trypsin, and chymotrypsin in the pyloric caecum and gut, and the relative expression levels of the related genes, increased first and then decreased, but the aspartate aminotransferase (ASP) and alanine aminotransferase (ALA) activity showed the opposite tendency. These reflected that the nutrient composition of gastrointestinal tract contents was dynamic, which caused obvious changes to the alpha diversity and structure of gastrointestinal microbiota. Lactobacillus, Acinetobacter, Bacteroides, Escherichia-Shigella, Prevotella, the genera represented by the Lachnospiraceae_NK4A136_group and MND1, Sphingomonas, Alistipes, Alloprevotella, Enterobacter, Helicobacter, Myroides, Ruminiclostridium, and Romboutsia were the main gastrointestinal microbiota based on the dominance, commonality, and colonization. The relative abundance of Lactobacillus and Acinetobacter in the three gastrointestinal tissues increased first and then decreased. According to the number of shared and dominant genera, the consistency of succession of some genera, and the increase in the similarity of microbiota structure among the three tissues, we inferred that the microbiota was affected by the gastrointestinal tract nutrient composition. Gastrointestinal microbiota genes were mainly enriched in the metabolism pathway according to the KEGG pathway, and the ratio of Firmicutes to Bacteroidetes, the representative of energy accumulation, followed an at-first increasing and then decreasing trend in each tissue. This shows that the main gastrointestinal microbiota played a synergistic role in the energy accumulation of the host. This study will provide a reference for the development of high-efficiency compound feed formulae and improve feed efficiency by regulating the gastrointestinal tract microecology for pond-cultured Japanese flounder.